1996
DOI: 10.1007/978-1-4899-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Finding Meaning in Dreams

Abstract: 10987654321All rights reservedNo part of this book may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, mechanical, photocopying, microfilming, recording, or otherwise, without written permission from the Publisher vii viii Preface be linked with studies of traumatic dreams and recurrent dreams to suggest there is a "repetition dimension" in dreams that tends to be overlooked because most theorists focus on one dream at a time. I also claim that studies of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
598
7
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(659 citation statements)
references
References 112 publications
(167 reference statements)
47
598
7
7
Order By: Relevance
“…Contrary to these models, there exists an extensive empirical literature indicating that waking and dreaming mentation are continuous [3,[12][13][14][15][16][17][18][19][20]. Numerous studies have demonstrated that when waking conditions are altered to reduce both external sensory input and the conscious demand for cognitive process (relaxed wakefulness), the resultant free-floating thought is quite similar to, and may even surpass, dreaming mentation in its imagistic-hallucinatory quality [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these models, there exists an extensive empirical literature indicating that waking and dreaming mentation are continuous [3,[12][13][14][15][16][17][18][19][20]. Numerous studies have demonstrated that when waking conditions are altered to reduce both external sensory input and the conscious demand for cognitive process (relaxed wakefulness), the resultant free-floating thought is quite similar to, and may even surpass, dreaming mentation in its imagistic-hallucinatory quality [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods to study the capacity for dream recall: the morning recall by means of brief questionnaires or dream diaries or the recall after dream interruption. Both methods, if applied to frequent dreamers, revealed consistent results 9,10 . However, this consistency does not occur in infrequent dreamers, for whom the capacity for recall is greater in provoked awakenings 10 .…”
Section: Dream Recallmentioning
confidence: 78%
“…Content analysis was performed on the dream reports using the Hall & Van de Castle definitions 39 to code the different activities 40 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations